Molecular Characterization and Expression Analysis of ftr01, ftr42, and ftr58 in Zebrafish (Danio rerio) - Liu, Wanmeng (Virol Sin, 2019)
Tripartite motif (TRIM) proteins were shown to play an important role in innate antiviral immunity. FinTRIM (ftr) is a new subset of TRIM genes that do not possess obvious orthologs in higher vertebrates. However, little is known about its function. In this study, we used bioinformatic analysis to examine the phylogenetic relationships and conserved domains of zebrafish (Danio rerio) ftr01, ftr42, and ftr58, as well as qualitative real-time PCR to examine their expression patterns in zebrafish embryonic fibroblast (ZF4) cells and zebrafish tissues. Sequence analysis showed that the three finTRIMs are highly conserved, and all contain a RING domain, B-box domain, and SPRY-PRY domain. In addition, ftr42 and ftr58 had one coiled-coil domain (CCD), whereas ftr01 had two CCDs. Tissue expression analysis revealed that the mRNA level of ftr01 was the highest in the liver, whereas those of ftr42 and ftr58 were the highest in the gill; the expression of these finTRIMs was clearly upregulated not in the eyes, but in the liver, spleen, kidney, gill, and brain of zebrafish following spring viremia of carp virus (SVCV) infection. Similarly, the expression of these three finTRIM genes also increased in ZF4 cells after SVCV infection. Our study revealed that ftr01, ftr42, and ftr58 may play an important role in antiviral immune responses, and these findings validate the need for more in-depth research on the finTRIM family in the future. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s12250-019-00112-5) contains supplementary material, which is available to authorized users.